Exploring the Intersection of Public Policy and Buddhist Philosophy in Thailand’s Social Welfare System - Niltakan, Kraingsak (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
This paper explores the intersection of public policy and Buddhist philosophy in shaping Thailand’s social welfare system. The integration of Buddhist principles such as compassion, mindfulness, and interdependence significantly influence the design and implementation of welfare policies aimed at addressing social challenges like poverty, inequality, and mental health. The paper examines how the Thai government’s social welfare programs reflect Buddhist values that prioritize collective well-being, ethical governance, and community care. With a focus on vulnerable groups, including the elderly, disabled, and teenage mothers, this study highlights the role of Buddhist philosophy in fostering inclusive and sustainable social policies. Additionally, the paper addresses the challenges of aligning modern public policy with Buddhist ideals, particularly in the face of globalization and economic pressures. By analyzing historical context and case studies, it presents a comprehensive view of how Buddhist thought continues to inform and guide social welfare practices in Thailand.